An Evaluation of the Effect of Waste Aluminum Sawdust on the Carbonation of Concrete - Demir, Tuba; Demirel, Bahar; Öztürk, Melek (My University, 2022)
The aim of this study is to examine the effect of replacing waste aluminum sawdust (AS) with fine aggregate on the strength and durability properties of concrete. For this, concrete mixtures with a cement dosage of 400 kg/m3 and water/cement (W/C) ratio of 0.40-0.50-0.60 were prepared. AS obtained from Elazig industrial site was added to the concrete mixtures by replacing 0%, 0.5% and 1% fine aggregate by volume. After curing in the curing pool for 28 days, the produced concrete samples were subjected to accelerated carbonation test in the carbonation tank at three different time periods the 1st, 3rd and 7th days. Compressive strength test and carbonation depth measurement test were performed on the samples before and after carbonation. In addition, the microstructure of AS concrete was investigated using scanning electron microscopic images (SEM). In the microscopic images, larger cracks, openings and interfacial voids were observed in the concrete matrix with the addition of AS. In addition, it has been observed that the carbonation effect contributes to the compressive strength
Keywords: İnşaat Mühendisliği; Malzeme Bilimleri; Özellik ve Test; Malzeme Bilimleri; Kâğıt ve Ahşap